The Impact of Problem Based Learning Methods on Long Jump Learning Outcomes for Primary School - Iqbal Husnayadi (Inspiree)
The  purpose  of  the study. The aim of this study was to determine the impact of the problem-based learning approach on the educational outcomes of the Primary School long jump students.